KEPEMIMPINAN TRANSFORMASIONAL DALAM UPAYA MENINGKATKAN KUALITAS SEKOLAH DAN KUALITAS TENAGA PENDIDIK - Dewi Retno Budiastuti (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2023)
Leadership in an organization is the ability to influence others. In school institutions, the Principal must be able to lead himself by having emotional and spiritual skills so that the Principal can run his school well. The principal must also be able to lead his team, namely teachers, employees and other school residents. Finally, the Principal must also be able to lead the organization, must be able to understand the vision and mission of the school well and have responsibility for the school he leads. The research method used in this study is a literature study. In this study, researchers search for data and information on various written sources including through archives, magazines, books, articles, news, journals or documents relevant to the problem studied. By conducting a literature study, researchers can have a broader and deeper deepening of the problem to be researched. In this study, researchers aim to determine efforts to improve the quality of schools and the quality of educators through transformational leadership. Main Duties and Functions of the Principal, which include planning and implementing work programs, supervising and evaluating, implementing leadership and implementing school information systems. All the main duties and functions carried out by the principal above, have the aim of improving the quality of the school. The principal as a transformational leader is someone who helps the organization and the people under his supervision to make good and positive changes in school activities. Change in an organization can occur slowly and also quickly. A teacher who works hard, will produce excellent work and results, and the quality of a good teacher can be seen from optimal work. Principals with transformational leadership will improve the quality of the school and also the quality of educators or teachers.